2013
DOI: 10.1590/0103-6440201302118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sealant Application and Thermal Cycling on Bond Strength of Tissue Conditioners to Acrylic Resin

Abstract: The aim of this study was to evaluate the effect of sealer application and thermal cycling on the bond strength between tissue conditioners and acrylic resin, and to observe the type of bond failure. Two hundred eighty-eight specimens (10x16x3 mm) were made of an acrylic resin (Lucitone 500, Dentsply) using a metal muffle. Specimens were divided into four groups according to the tissue conditioner (Coe-Comfort, GC or Dentusoft, Densell) used and whether or not a sealer (Eversoft Soft Liner Sealer, Myerson) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…[13][14][15] It has been shown that over a period of 1 week, water sorption increased from 0.2 to 5.6 mg/cm, and solubility ranged from 0.03 to 0.40 mg/cm for various commercial products. [16][17][18] One of the main problems with silicone-based TCs concerns bonding to the denture base surface. It has been shown that "adhesion" between the lining mate-rial and base of the denture is the most common source of failure of a resilient-lined denture.…”
Section: Physical Properties Of Tcsmentioning
confidence: 99%
“…[13][14][15] It has been shown that over a period of 1 week, water sorption increased from 0.2 to 5.6 mg/cm, and solubility ranged from 0.03 to 0.40 mg/cm for various commercial products. [16][17][18] One of the main problems with silicone-based TCs concerns bonding to the denture base surface. It has been shown that "adhesion" between the lining mate-rial and base of the denture is the most common source of failure of a resilient-lined denture.…”
Section: Physical Properties Of Tcsmentioning
confidence: 99%
“…Akin et al reported that lasers were more effective than chemicals of the liner. Sampaio et al evaluated the bond strength of acrylic‐based resilient lining material to PMMA by using a tensile test and reported similar results between chemicals of the liner and control. Minami et al evaluated the bond strength of silicon‐based resilient lining material to PMMA by using tensile test and reported that chemicals of the resilient liner increased the bond strength, but reduced the bond strength if supported by sandblasting.…”
Section: Discussionmentioning
confidence: 91%
“…Light curing was performed on each respective side for 40 s using a light-cure machine (Demetron Optilux 401, Kerr, USA). The samples were divided into two groups: (1) the as-prepared dried samples from curing, which were tested immediately; and (2) the wet samples, which were obtained by further immersing the cured specimen in deionized water at 37°C beyond the initial 24 h immersion, followed by thermal cycling (600 and 2400 cycles, 5°C/55°C, 2 min/cycle; Long Wha Enterprise Co., Kaohsiung, Taiwan) [22]. The water baths were used to prevent ion effects and evaluate auto-mineralization.…”
Section: Physiochemical Analysesmentioning
confidence: 99%
“…To investigate the aging process of the composite resins, the effect of mineralization and the efficiency of silane-modified nanocrystals in composite resins during thermal cycling were evaluated. Although the thermal fatigue numbers of thermal cycling varied in large ranges depending on the applied condition and restorative sites, cycling time ranges from 100 to 12000 cycles [22][23][24][25]. Thermal cycling is generally used to simulate the temperature fluctuations that occur in the oral cavity to generate stress and to determine the changes in the properties of the prosthetic materials with age [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation